Choice of local anesthetic in obstetric anesthesiology: literature review and demonstration of our own experience - Grizhimalskiy, E; Harha, A (Pain medicine, 2022)
Regional anesthesia is widely used in obstetric practice, and in many cases is the method of choice. It includes neuroaxial anesthesia (spinal, epidural, combined spinalepidural, epidural with dura mater puncture), regional blocks (eg, TAP block, QL block, ESP block, pudendal block, etc.), as well as local infiltration anesthesia, which is used for both anesthesia and postoperative analgesia. The correct choice of local anesthetic, its dose and concentration is of fundamental importance in obstetric anesthesiology, as it is necessary to ensure the highest quality blockade with minimal side effects on mother and fetus.